Depression in the House: The Effects of Household Air Pollution from Solid Fuel Use in China - Yan Liu; Xi Chen; Zhijun Yan (Institute of Labor Economics (IZA), 2019)
While adverse health effects of ambient air pollution have been well documented, there is scarce evidence on the impact of household air pollution (HAP) on mental health. We investigated the causal link between HAP exposure from the use of solid fuel on depressive symptoms using a nationally representative dataset of middle-aged and older population in China. Employing the Propensity score matching (PSM), matching and adjusting for potential confounders, we found significantly higher Center for Epidemiological Studies Depression Scale (CES-D) score and risk of depressive symptoms among solid fuel users than clean fuel users. These associations were especially stronger for older females who were less educated, of lower income, of higher body mass index, or had chronic diseases.
Keywords: I31; Q51; Q53; 330; propensity score matching; household air pollution; household solid fuel use; depression; CHARLS